Academic Literacy in Physics Teacher Education: Integrating ESP and Self-Efficacy - Rachmawati Putri Ainiyah; Zahra Dhabithah; Wahyunengsih (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
English competence is increasingly necessary for prospective physics teachers who must engage with international scientific literature. While prior studies have reported general English difficulties among non-English majors, limited attention has been given to how discipline-specific language demands and self-efficacy jointly shape academic literacy in physics teacher education. This study addresses this gap by examining the English skills most required by pre-service physics teachers and their perceptions of their own proficiency. A mixed-method descriptive survey involving 41 undergraduate students was conducted using a Likert-scale and open-ended instruments. The findings show that reading is perceived as the primary need (M = 4.54), particularly for accessing journals and textbooks, followed by academic vocabulary awareness. However, participants reported challenges in mastering technical terminology and producing scientific explanations in written and oral forms. These results indicate a persistent awareness–competence gap and suggest that academic literacy in physics education should be understood as an integrated construct combining disciplinary reading demands, specialized vocabulary development, productive communication skills, and self-efficacy. The study contributes to ESP and EAP discussions by emphasizing the role of technical vocabulary in linking comprehension with academic production within science-specific contexts.